Transforming Ideas into Start up s UMPSA Students in Launch X Programme@ SunwayUniversity - Nor Saradatul Akmar, Zulkifli (Faculty of Computing, 2024)
Student from the Faculty of Computing are among the 3 student entrepreneurs selected to participate in the Launch X Programme, organized by Sunway University in collaboration with Universiti Teknologi Malaysia (UTM) and the Ministry of Higher Education (KPT).